2020
DOI: 10.1103/physrevb.102.014404
|View full text |Cite
|
Sign up to set email alerts
|

Scaling the electrical current switching of exchange bias in fully epitaxial antiferromagnet/ferromagnet bilayers

Abstract: While the electrical current manipulation of antiferromagnets (AFMs) has been demonstrated, the extent of the studied AFM materials has been limited with few systematic experiments and a poor understanding. We compare the electrical current switching of the exchange-bias field (Hex) in AFM-Mn3AN/ferromagnet-Co3FeN bilayers. An applied pulse current can manipulate Hex with respect to the current density and FM layer magnetization, which shifts exponentially as a function of the current density. We found that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…The coexistence of Γ 5g and M-1 phase below the FM-like transition temperature has also been previously reported [28]. As the MGN/FM bilayers exhibit an exchange bias at 4 K [29], it is concluded that Γ 5g order and M-1 phase coexist below 200 K.…”
Section: A Film Characteristics and Magnetotransport Propertiessupporting
confidence: 82%
“…The coexistence of Γ 5g and M-1 phase below the FM-like transition temperature has also been previously reported [28]. As the MGN/FM bilayers exhibit an exchange bias at 4 K [29], it is concluded that Γ 5g order and M-1 phase coexist below 200 K.…”
Section: A Film Characteristics and Magnetotransport Propertiessupporting
confidence: 82%
“… [135] in Pt/IrMn/CoFeB, which can be proposed in IMA-MTJs. Subsequently, many efforts have been made to electrically control EB fields in other structures such as IrMn/NiFe [136] , Pt/Co/NiO [137] , and AFM-Mn 3 AN/FM-Co 3 FeN bilayers [138] . Moreover, all-optical control of the magnetization and EB fields in IrMn/[Co/Pt]xN heterojunctions was realized by Vallobra et al.…”
Section: The Birth Of Next-generation Afm-based Devicementioning
confidence: 99%
“…It has already been established that AFM systems exhibit several exotic quantum phenomena, replacing the traditional FM samples, like spin Seebeck effect [30], spin Hall effect [31][32][33][34], spin filtration [35], spin transfer torque [36,37], high frequency dynamics [23,24,38], memory applications [22], and to name a few [39][40][41][42][43][44][45][46][47]. Considering these phenomena, a question arises that can we also establish spin dependent circular current [48][49][50][51][52][53], another novel aspect in nanoscale, in a magnetic conducting ring possessing 'vanishing net magnetization' and even when there is no spin chirality.…”
Section: Introductionmentioning
confidence: 99%